ANALISIS CARA BELAJAR SISWA BERPRESTASI TINGGI DI SDN 2 KARANGSAMBUNG - Melta Sintala; Fajar Nugraha; Hatma Heris Mahendra (Institut Nahdlatul Ulama Tasikmalaya, 2023)
The background of this research is that school is a development of ways of behaving and abilities that exist in students. Education is an important thing for humans and is the main need to obtain information and learning exercises even though in reality learning can be done anywhere and can not only be obtained through learning at school. This study aims to find out how to learn about achieving students and the factors that can influence these students in their learning activities and is expected to provide an overview of the learning strategies of achieving students and the factors that influence how achieving students learn by using qualitative methods through observation, meetings, and documentation by taking sample 29 students consisting of 12 boys and 17 girls in class IV SDN 2 Karanggulung. The end result of this study is that achievers are very used to making student notebooks and reviewing the lessons learned the previous day and then always completing assignments given by the teacher and being able to manage time to divide up their daily activities and also always rest to maintain health and gain support from family, friends and environment. Keywords: Step by step instructions to learn understudies, understudy accomplishment, Characteristics of outstanding students' learning